ANALISIS BRANDED CONTENT VIDEO (BCV) SEBAGAI STRATEGI MARKETING UNTUK GENERASI Z DI JABODETABEK - Jannah, Fani Nur; Amorza, Sabrina; Pinontoan, Vintasya Hilda Kauri (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This study aims to analyze the impact of branded content videos on the purchasing interest of Generation Z. This research is conducted because, according to BPS, Generation Z will become the most populous generation by 2030, a phenomenon often referred to as the demographic bonus. Therefore, a study is needed to understand the characteristics of Generation Z to develop a digital marketing strategy, particularly in creating branded content videos (BCV) on social media. This research uses a qualitative method with descriptive analysis. The unit of analysis is Generation Z individuals who frequently use social media for shopping and are often exposed to promotional videos of products marketed on social media. The results of this study show that branded content videos that are relatable, high-quality, objective, organic, and beneficial are more appealing to Generation Z than videos by influencers or celebrities promoting a product, especially evident in advertising videos that overtly market products.